Influence of the human-machine-environment system on reliability automated systems IAB of the Russian Federation - A. I. Yangirov; I. M. Yangirov; I. G. Drovnikova; V. R. Romanova; P. M. Duplyakin (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. The article examines the influence of the “man-machine-environment” system on the reliability of automated systems of internal affairs bodies of the Russian Federation.Method. The study was conducted based on an analysis of possible human and technical factors, as well as environmental factors affecting the reliability of automated systems, various sources of scientific literature and publications.Result. The result of the automated system for calculating the security index of the analyzed open OS is one of the specified criteria for the degree of security of the OS, based on the provisions of fuzzy logic.Conclusion. The calculation results demonstrate that replacing even one element allows increasing the overall reliability of the automated system. In the example of the considered ACS, the overall reliability of the automated system increased by 18%.